Unraveling Anthropocene Paleoenvironmental Conditions Combining Sediment and Foraminiferal Data: Proof-of-Concept in the Sepetiba Bay (SE, Brazil) - Silva, Layla Cristine da; Alves Martins, Maria Virgínia; Figueira, Rubens; Frontalini, Fabrizio; Pereira, Egberto; Senez-Mello, Thaise M.; Castelo, Wellen Fernanda Louzada; Saibro, Murilo Barros; Francescangeli, Fabio; Mello e Sousa, Silvia Helena; Bergamaschi, Sérgio; Antonioli, Luzia; et al. (Frontiers in Ecology and Evolution, 2022)
from the direct oceanic action by a barrier island and several islands. The SB is highly anthropized and due to its great environmental, economic and social importance has been the target of several works aiming to study the sources of pollution and its environmental impact. The objectives of the present study were to infer the paleoenvironmental changes by a multiproxy approach (granulometric, mineralogical, geochemical and foraminiferal data) and a robust age model based on 210Pb and 137Cs data along the core SP5, collected in the inner central region of the SB. The evolution of the area has been quite complex; in the first half of the 20th century; it was influenced by the sedimentary processes associated to the Guandu River delta, whose mouth should have been located closer to the study area; it went through subaerial processes, through phases of greater or lesser influence of continental waters and later through marine overwash events. The moderate enrichment in lithogenic elements in this period should have been related not only to weathering and erosion of rocks but also to mining activities in the region. Since the second half of the 20th century, the study area has been more influenced by oceanic processes, but it has undergone progressive siltation processes due to anthropogenic interventions in river courses, eutrophication and metal pollution. The weak hydrodynamic conditions favored the progressive development of low diversified benthic foraminiferal assemblages composed mainly by opportunist species. The paleoecological conditions base on foraminiferal diversity metric were poor around 1970, worsened after the metal spill released by the largest polluting company, the Inga Mercantil, and after that progressively improved and became good in 2015. The results of this work indicate that the study site is recovering after a phase of major environmental impact. This work shows that benthic foraminifera and their application may represent a very useful tool to track paleoenvironmental changes and the evaluation of palaeo-ecological quality status.